FACTORS AFFECTING EMPLOYEE JOB SATISFACTION IN UNIVERSITIES IN SOMALIA - AHMED, HILOWLE ABDULLAHI; GICHINGA, Dr LUCY (IJRDO - Journal of Business Management, 2016)
the main purpose of this study was to investigate the factors affecting employeejob satisfaction in universities in Mogadishu-Somalia with a specific reference to MogadishuUniversities-Somalia. This study was guided by the following three research questions: What isthe influence of organizational culture on employee job satisfaction in universities inMogadishu- Somalia? What is the influence of work environment on employee job satisfactionin universities in Mogadishu- Somalia? How does the leadership style influence employee jobsatisfaction in universities in Mogadishu-Somalia? A descriptive research design was beingadopted. The dependent variable was employee job satisfaction while the independent variableswere organizational culture, work environment and leadership style factors of employee jobsatisfaction. Proportionate stratified random sampling technique was used . The results revealthat organizational culture , work environment and leadership style have significant andpositive effects on employee job satisfaction, while organizational culture have insignificanteffects on employee job satisfaction in the universities in Mogadishu Somalia.